Synthesis and characterization of layered Li（Ni1/3Mn1/3CO1/3）O2 cathode materials by spray-drying method - 刘智敏 胡国荣 彭忠东 邓新荣 刘业翔 (Transactions of Nonferrous Metals Society of China, 2007)
Spherical Li（Ni1/3Mn1/3Co1/3）O2 was prepared via the homogenous precursors produced by solution spray-drying method. The precursors were sintered at different temperatures between 600 and 1 000 ℃ for 10 h. The impacts of different sintering temperatures on the structure and electrochemical performances of Li（Ni1/3Mn1/3Co1/3）O2 were compared by means of X-ray diffi＇actometry（XRD）, scanning electron microscopy（SEM）, and charge/discharge test as cathode materials for lithium ion batteries. The experimental results show that the spherical morphology of the spray-dried powers maintains during the subsequent heat treatment and the specific capacity increases with rising sintering temperature. When the sintering temperature rises up to 900 ℃, Li（Ni1/3Mn1/3Co1/3）O2 attains a reversible capacity of 153 mA·h/g between 3.00 and 4.35 V at 0.2C rate with excellent cyclability.